As elites acadêmicas na ciência climática brasileira - Antonio, Luiz Felipe Alves (Universidade Federal de São Carlos, 2022)
This dissertation analyzes the scientific elites involved in the production of knowledge regarding meteorological and climate information in Brazil. To this do so, it was necessary a prior study of some currents of thought around the theme of the elites, a theme that is among the main issues discussed in the science since the end of the 19th century, and throughout the 20th century. Among the main currents of thoughts, stands out Pierre Bourdieu, since his work, together logic of the prosopographic methodology, provided the necessary means for a analysis of the Center for Weather Forecasting and Climate Studies (CPTEC), which is linked to national institute of space research (INPE). To this do so, it was necessary to present the origin, formation and trajectory of some of its main exponents, in order to bring this discussion to the academic debate with the aim of responding to how was the emergence of scientific careers in this group; as well as what the impacts of consolidation of an "elite" in the field of Brazilian climate science. We will investigate the characteristics of the CPTEC team in the period 2001-2010 with the objective of understand what are the essential leaders in the process of training and consolidation of the group of symbolically dominant researchers responsible for the production of data and information essential for monitoring, advancing and controlling studies Brazilian climate change
Academic elites in brasilian climate science
Keywords: Elites científicas; CIENCIAS HUMANAS::CIENCIA POLITICA::POLITICAS PUBLICAS